OPTIMALISASI WHATSAPP BUSINESS DAN INSTAGRAM MARKETING BAGI UMKM DI KELURAHAN TIRTO KOTA PEKALONGAN - VICTORIANUS ARIES SISWANTO; Tri Pudji Wahjuningsih; Era Yunianto (BESTIKOM Jurnal Pengabdian Kepada Masyarakat, 2026)
Usaha Mikro, Kecil, dan Menengah (UMKM) play an important role in the local economy, including in Tirto Village, Pekalongan City. The development of digital technology and changes in consumer behavior require UMKM actors to utilize digital media as a marketing and communication tool. WhatsApp Business and Instagram Marketing are accessible and widely used platforms; however, their utilization by UMKM in Tirto Village is still not optimal. UMKM actors have not fully understood the features of WhatsApp Business, such as product catalogs, automated messages, and customer labels. In addition, the implementation of Instagram Marketing is still constrained by challenges in creating attractive and consistent content aligned with platform algorithms, as well as limited understanding of digital marketing strategies, including the use of hashtags, analytical insights, and call-to-action techniques. This condition indicates that the potential of digital marketing has not been utilized optimally. Therefore, the Community Service Implementation Team of Institut Widya Pratama organized training on the utilization of WhatsApp Business and Instagram Marketing for UMKM in Tirto Village. This activity aimed to improve the knowledge and skills of UMKM actors in managing both platforms as effective and sustainable digital marketing strategies. The training contributed to increasing business visibility, strengthening customer relationships, and supporting the sustainability and competitiveness of UMKM in the future. The post-test results showed an improvement in participants’ ability to use WhatsApp and Instagram for business promotion, increasing from 64.7% to 90%. Kata Kunci : UMKM, pemasaran digital, WhatsApp Business, Instagram Marketing, pengabdian kepada masyarakat